2006
DOI: 10.1016/j.jdent.2005.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Bracket bond strength dependence on light power density

Abstract: In order to reduce curing time for bracket bonding with light-cured composites, manufacturers increase the power density (PD) of light sources. The present study aims at investigating the relationship between PD and shear bond strength (SBS) at short exposure time

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 22 publications
(47 reference statements)
1
24
0
Order By: Relevance
“…9 Advances in technology have made it possible to increase light power density and thus reduce the necessary duration of exposure without compromising bonding efficacy. Recently, a high-power water-cooled halogen light with shorter curing times and an increased performance of 3000 mW/cm 2 was introduced (Swiss Master Light, EMS Electromedical Systems, Nyon, Switzerland).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Advances in technology have made it possible to increase light power density and thus reduce the necessary duration of exposure without compromising bonding efficacy. Recently, a high-power water-cooled halogen light with shorter curing times and an increased performance of 3000 mW/cm 2 was introduced (Swiss Master Light, EMS Electromedical Systems, Nyon, Switzerland).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a high-power water-cooled halogen light with shorter curing times and an increased performance of 3000 mW/cm 2 was introduced (Swiss Master Light, EMS Electromedical Systems, Nyon, Switzerland). 10 Staudt et al 9,11 suggested that a 6-second cure time, and even-with caution-a 3-second cure time might be adequate for bonding orthodontic brackets to tooth enamel using this new high-power halogen light.…”
Section: Introductionmentioning
confidence: 99%
“…Advantages considering resistance to tensile and shear bonding strength when blue LEDs systems are used are necessary to be shown to justify their use in clinical procedures, because brackets are under tensile and shear mechanical forces during the entire treatment [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Adequate light exposure should result in a biocompatible restoration with the manufacturers' intended physical properties and clinical longevity. If insufficient light reaches the resin, inadequate polymerization of the resin occurs, 1 which adversely affects both the physical and chemical properties of the restoration 2–9 . A poorly polymerized restoration may result in premature clinical failure because of marginal defects, secondary caries, or restoration fracture.…”
Section: Introductionmentioning
confidence: 99%